Labyrinths and Tangled Paths. The Story of a Righteous One - Barbara Engelking (Zagłada Żydów)
The article tells the story of Henryk Ryszewski, who provided hiding to about a dozen Jews in his flat in the Warsaw district of Mariensztat. Accused after the war of blackmailing Jews (as I think, wrongly), he was convicted and spent several years in prison. His prosecutor fell victim of the ‘paper industry affair’ show trial and also spent a few years in prison.